PENGARUHPENGALIHANPAJAKBUMI DANBANGUNANPERDESAAN DANPERKOTAAN TERHADAPBELANJAMODAL DENGANPENDAPATANASLIDAERAH SEBAGAIVARIABEL PEMODERASI (StudiEmpirispada Kabupaten/KotadiProvinsiAceh) - Unazir Achmad Zikri; Jhon Andra Asmara (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
Thisstudyaimedto examinetheeffectofthetransitiontaxlandandbuildinginvillage and citytowards capitalexpenditurewithregionalrealrevenueasthemoderatingvariable.Thedatausedin thisresearchhis secondarydata.Thesamplewastakenby purposivesamplingmethodand thenumberofsamplesobtained were17 district/cityintheprovinceofAcehin2014 and  2015.Theanalysistechniqueusedismoderatedregression analysisusingSPSS 23.This study uses tax land and building in village and city as the independent  variable and capital expenditureasthedependentvariable,andthenregionalrealrevenueasthemoderatingvariable.Theresultsof thisstudy indicatethatthe simultaneoustesting(testF),taxlandandbuildinginvillageandcityandregionalreal revenuehasaneffectoncapitalexpenditure.Inthepartialtest(ttest),variabletaxlandandbuildinginvillage andcityandregionalrealrevenuehasno effectoncapitalexpenditure. Keywords:Tax land and building invillage and city, capital expenditure ,and regional real revenue